ANALISIS KEMAMPUAN LITERASI SAINS SISWA PEMBELAJARAN BIOLOGI PADA SMAN DI KABUPATEN BONE - Saparuddin; Nurul Jihani; Abd. Muis (Jurnal Biogenerasi, 2023)
This study aims to determine the scientific literacy ability of students in biology learning at SMAN 1 Bone. The research method used is descriptive quantitative research method. The population of this research is all students of MIPA class at SMAN 1 Bone. The research sample was 102 class XII students with jenuh sampling technique of determining the sample. The data collection technique was in the form of multiple choice test questions for students' scientific literacy skills with a total of 30 questions. Based on the research that has been carried out on SMAN 1 Bone students, it can be concluded that the highest scientific literacy ability of SMAN 1 Bone students is in the medium category with the correct percentage of 77.4%. This means that some students in Bone Regency are able to think rationally and scientifically to solve a problem at hand. this indicates that some students have understood in managing their knowledge to solve various problems by making decisions based on scientific considerations